(3JMaI GdeMHjf hGdCUMGH ajeG ddeOfjjf ef GdBfSGHs - (3GdWQGHdSj , YHO GdQMef Hf YHO GdcQje GdeUjQGJjs
(3ChdgG (B:s
(3GdMeO ddg GdPi CdHS LjQGe fHjg GdcQje CaNQ LdHGH s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B146s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B98 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs